Opening Up in the Caucasus and Central Asia : Policy Frameworks to Support Regional and Global Integration - Kunzel, Peter (Departmental Papers; Departmental Paper ;, 2018)
The Caucasus and Central Asia (CCA) countries are at an important juncture in their economic transition. Following significant economic progress during the 2000s, recent external shocks have revealed the underlying vulnerabilities of the current growth model. Lower commodity prices, weaker remittances, and slower growth in key trading partners reduced CCA growth, weakened external and fiscal balances, and raised public debt. the financial sector was also hit hard by large foreign exchange losses. while commodity prices have recovered somewhat since late 2014, to boost its economic potential, the region needs to find new growth drivers, diversify away from natural resources, remittances, and public spending, and generate much stronger private sector-led activity.